Edukasi Pengenalan Akad Dalam Transaksi Syariah Serta Pengenalan Pembiayaan Syariah Online Guna Penguatan Modal Bagi Para Pelaku UMKM Di Desa Sebewe Kecamatan Moyo Utara - Hanifa Sri Nuryani; Sudrajat Martadita; Fadli Faturrahman; edi edi (CV. Multi Kreasi Media, 2022)
This community empowerment activity was carried out in Sebewe Village, North Moyo District, Sumbawa Regency. Based on the results of community service activities with the theme